2010
DOI: 10.1590/s0102-695x2010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do sequestro do óxido nítrico (NO) pelo extrato metanólico da alga Bryothamnion triquetrum (Gmelin) Howe

Abstract: RESUMO: O excesso de óxido nítrico (NO) produzido por indução da enzima óxido nítrico sintase (iNOS) participa do desenvolvimento de inúmeras desordens que conduzem à perda da homeostasia. O estresse oxidativo gerado pelo aumento da produção endógena de NO pode levar a efeitos de toxidade induzida, tais como peroxidação lipídica, nitração de proteínas e danos ao DNA. Compostos que sejam capazes de sequestrar o radical NO podem diminuir a toxicidade das espécies reativas de nitrogênio (RNS), atuando na modulaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Some studies have demonstrated an antioxidant action [76,77,78,79,80] and nitric oxide (NO) scavenging for B. triquetrum [79]. ROS, including molecules such as hydrogen peroxide, superoxide, hydroxyl radicals and NO, have been implicated in tissue damage and development of the inflammatory and pain response.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated an antioxidant action [76,77,78,79,80] and nitric oxide (NO) scavenging for B. triquetrum [79]. ROS, including molecules such as hydrogen peroxide, superoxide, hydroxyl radicals and NO, have been implicated in tissue damage and development of the inflammatory and pain response.…”
Section: Resultsmentioning
confidence: 99%
“…It is related to several pathological processes, including inflammatory processes and induced toxicity (ADEGBOLA et al, 2017;FÖRSTERMANN et al, 2017;MITTAL et al, 2014;SILVA, DELGADO, 2020). Thus, the search for natural substances capable of scavenging free radicals can be of great value in the therapeutic field, helping to reduce the toxicity caused by reactive species, acting as a modulator of inflammatory processes (MAIA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%